Vegetable production under COVID-19 pandemic in China: An analysis based on the data of 526 households - Jie-hong ZHOU; Fei HAN; Kai LI; Yu WANG (Journal of Integrative Agriculture, 2020)
The COVID-19 pandemic had an enormous impact on the vegetable supply chain in China. Effective evaluation of the pandemic's influences on vegetable production is vital for policy settings to enhance the security of vegetable supply. Based on first-hand data from 526 households, we explored regional differences in different types of loss and potential factors affecting the severity farmer households suffered during the pandemic. The results underline that sales contraction and price volatility in the context of interruption of supply chain dominate the total losses during the pandemic. Such losses differ across provinces and are more substantial in provinces with stricter confinement measures. Farmer households' participation in local market and modern marketing methods helps mitigate the negative effects of the COVID-19 shock, while labor hiring and facilities adoption in production widen the losses due to the shortage in the workforce. In the future, the vegetable industry practitioners and relevant government departments should work together to coordinate the development of short and long supply chains and strengthen the stability and security of the vegetable supply chain.